Careers in ecology: a fine‐scale investigation of national data from the U.S. Survey of Doctorate Recipients. Issue 12 (21st December 2017) - Hampton, Stephanie E.; Labou, Stephanie G.
Abstract: For several decades, economists have been warning the academic community that graduate training has been too tightly focused on careers in higher education, using the apprenticeship model in which students are trained to become tenure‐track faculty at research‐focused institutions. These jobs are simply not growing at the same rate as graduate admissions. In biomedical research, the mismatch in supply and demand has now been widely recognized. Other disciplines have begun these discussions, but for smaller fields, employment trends are more difficult to identify because they are subsumed in aggregated national statistics. For non‐biomedical biological fields in particular, such as ecology, using biology statistics may be inappropriate since trends within the field may be obscured by the strong signal from biomedical disciplines. Here, we use the 2013 Survey of Doctorate Recipients (SDR) to investigate career paths for ecology Ph.D. recipients in the United States, and present the first fine‐scale national profile of careers in ecology. Our results demonstrate that while involuntary unemployment is low for ecology Ph.D. recipients (3.3%) and job satisfaction is high, the assumptions of the prevailing apprenticeship model are inappropriate: Less than 20% of employed recent ecology Ph.D. graduates are in tenure‐track positions at a Ph.D.‐granting university. Accordingly, proactive steps could be taken to create more realistic expectations about graduate training and preparation for diverse careers. Further, the SDR data provide demographic profiles for ecology. Ethnic diversity has remained low in ecology (7.5% non‐Caucasian for Ph.D. recipients since 2000). Gender balance in career‐track positions appears to have improved by multiple metrics. However, women are overrepresented in non‐tenure‐track academic positions, where access to resources that support professional advancement may be limited relative to tenure‐track jobs, and salary disparities appear for women in private academic institutions. Thus, while there is much good news in these data, we suggest that ecology as a field would benefit from (1) a broad analysis of the training required to make Ph.D.s best prepared for jobs outside of the research‐oriented tenure track and (2) continued attention to increasing diversity and equity.